2002
DOI: 10.1051/0004-6361:20011526
|View full text |Cite
|
Sign up to set email alerts
|

The outer evolution of instability-generated structure in radiatively driven stellar winds

Abstract: Abstract. We investigate stochastic structure in hot-star winds. The structure (i.e. inhomogeneities such as clumps and shocks) is generated by the instability of the line driving mechanism in the inner wind. It is self-excited in the sense that it persists even in the absence of explicit perturbations. The evolution of structure as it moves out with the flow is quantified by the radial dependence of statistical properties such as the clumping factor and the velocity dispersion. We find that structure evolves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
218
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(245 citation statements)
references
References 28 publications
24
218
1
2
Order By: Relevance
“…On the other hand, a detailed numerical study of wind stability (cf. Feldmeier et al 1997;Runacres & Owocki 2002), and of effects of stellar rotation on the stellar wind (cf. Petrenz & Puls 2000) showed that basic wind parameters (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a detailed numerical study of wind stability (cf. Feldmeier et al 1997;Runacres & Owocki 2002), and of effects of stellar rotation on the stellar wind (cf. Petrenz & Puls 2000) showed that basic wind parameters (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…neglect of wind non-stationarity (cf. Runacres & Owocki 2002), wind 3D structure (Dessart & Owocki 2003), or wind magnetic fields (ud-Doula & Owocki 2002). Among these unsolved problems is the long-standing momentum problem of WR stars (for the latest progress see Gräfener et al 2002) or problems with fitting of X-ray line profiles (Kramer et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is the result of a positive feedback in which a small increase in the velocity of a fluid parcel exposes the parcel to more intense, unattenuated radiation from the star and causes it to be further accelerated (Owocki et al 1988;Feldmeier 1995;Owocki & Puls 1996, 1999. Simulations of this self-excited wind instability show that the gas compression in clumps typically starts at about 0.3-0.4 ∞ and can extend to very large radii (Runacres & Owocki 2002). These simulations, however, do not account for (transonic) velocity curvature terms.…”
Section: Clumping Factormentioning
confidence: 98%
“…Similar conclusions have been reached for some Otype stars (e.g., Hillier et al 1993). Detailed hydrodynamic simulations are now needed to determine whether instability-generated wind shocks can persist to hundreds of radii in W-R stars, analogous to those recently undertaken for OB stars by Runacres & Owocki (2002).…”
Section: Radiative Wind Shocksmentioning
confidence: 99%